Drug-drug interactions : scientific and regulatory perspectives - Li, A. P. (Advances in pharmacology, 1997)
Drug-Drug Interactions is a comprehensive review of the scientific and regulatory perspectives of drug-drug interactions from the point-of-view of academia, industry, and government regulatory agencies. This book is intended for professionals in the pharmaceutical industry, health care, and governmental regulatory agencies. Topics of interest include the mechanistic understanding of drug-drug interactions, the prediction of drug-drug interaction potential of new drugs, and the avoidance of clinically significant drug-drug interaction in patients. Key Features * Provides useful references on the science of drug-drug interactions * Describes in a basic and comprehensive manner drug-drug interactions from the mechanistic viewpoint * Contains original data from academic and industrial laboratories * Presents an overview of regulatory agency positions.